The Making of a Dealer Market: From Entry to Equilibrium in the Trading of Nasdaq Stocks - Ellis, Katrina; Michaely, Roni; O'Hara, Maureen (Journal of Finance, 2002)
ABSTRACT This paper provides an analysis of the nature and evolution of a dealer market for Nasdaq stocks. Despite size differences in sample stocks, there is a surprising consistency to their trading. One dealer tends to dominate trading in a stock. Markets are concentrated and spreads are increasing in the volume and market share of the dominant dealer. Entry and exit are ubiquitous. Exiting dealers are those with very low profits and trading volume. Entering market makers fail to capture a meaningful share of trading or profits. Thus, free entry does little to improve the competitive nature of the market as entering dealers have little impact. We find, however, that for small stocks, the Nasdaq dealer market is being more competitive than the specialist market.